2004
DOI: 10.1081/ada-200037548
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Methadone Maintenance Treatment Outcomes Using the Addiction Severity Index and the MMPI‐2 Content Scales (Negative Treatment Indicators and Cynism Scales)

Abstract: We studied the ability of the Minnesota Multiphasic Personality Inventory-2 Content Scales (Negative Treatment Indicators [TRT] and Cynicism [CYN]) and the domain scales of the Addiction Severity Index (ASI) in predicting outcome from a methadone maintenance program. Participants were 108 African American males treated in a VA health care outpatient methadone maintenance treatment program and followed for up to 1 year after admission. Dependent variables were 1) length of stay and the percentage of 2) missed m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 20 publications
0
15
0
1
Order By: Relevance
“…For example, McCaul, Svikis, and Moore (2001) found that race, sex, and employment status, but not substance use patterns, predicted treatment participation and retention among adult patients admitted to an outpatient substance abuse treatment clinic. Craig and Olson (2004) found that drug severity and psychological domain scores on the Addiction Severity Index (ASI) predicted attendance among persons enrolled in an outpatient methadone maintenance program. Higher functional support on intake has also been shown to be a modest positive predictor of treatment retention and alcohol use reduction, but not drug use reduction, among clients admitted to an outpatient treatment program (Dobkin, Civita, Paraherakis, & Gill, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…For example, McCaul, Svikis, and Moore (2001) found that race, sex, and employment status, but not substance use patterns, predicted treatment participation and retention among adult patients admitted to an outpatient substance abuse treatment clinic. Craig and Olson (2004) found that drug severity and psychological domain scores on the Addiction Severity Index (ASI) predicted attendance among persons enrolled in an outpatient methadone maintenance program. Higher functional support on intake has also been shown to be a modest positive predictor of treatment retention and alcohol use reduction, but not drug use reduction, among clients admitted to an outpatient treatment program (Dobkin, Civita, Paraherakis, & Gill, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Clients who reported higher levels of preadmission substance use are more likely to report use of these substances at follow-up than their counterparts (Ottomanelli, 1999). Higher addiction severity scores (alcohol and drug use) are also correlated with poorer MMT outcome (Craig and Olson, 2004). …”
Section: Introductionmentioning
confidence: 99%
“…Findings with regard to these variables using standardized assessment instruments have been mixed. Whereas factors related to amenability have consistently demonstrated relationships to poor treatment outcome, research on treatment motivation has received more mixed results using both performance-based (e.g., Rorschach: Ackerman, Hilsenroth, Baity, & Blagys, 2000;Alpher, Perfetto, Henry, & Strupp, 1990;Hilsenroth, Handler, Toman, & Padawer, 1995;Nygren, 2004;Viglione, 1999) and self-report (e.g., Minnesota Multiphasic Personality Inventory [MMPI]: Chisholm, Crowther, & Ben-Porath, 1997;Craig & Olson, 2004;Geer, Becker, Gray, & Krauss, 2001;Gilmore, Lash, Foster, & Blosser, 2001;Hilsenroth et al, 1995;Minnix et al, 2005) methods. For example, although the MMPI-2 Negative Treatment Indicators scale was designed to evaluate problematic client beliefs about psychotherapy, including low motivation for change, it has been somewhat effective in predicting treatment problems in some studies (e.g., Gilmore et al, 2001) but ineffective in several others (e.g., Hilsenroth et al, 1995;Minnix et al, 2005).…”
mentioning
confidence: 99%